BRT System in Uberaba- MG: Service efficiency and impacts on the real estate and tertiary sectors - Mendes, Fúlvia Maria; Costa , Carolina Carrijo; Garrefa, Fernando (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Bus Rapid Transit (BRT) consists of the design of exclusive bus lanes on high-density routes, intending to increase the supply and speed of buses. The system has been popularized for improving public transport and has already been adopted by several cities around the world. Despite the benefits, the implementation of BRT can have important impacts on the city related to the need for a robust road structure, such as sectioning the urban fabric, changes in land use and landscape, reduced local accessibility for pedestrians, as well as disrupting established road, real estate, and commercial dynamics. Considering these issues, this article aims to investigate the changes in space and urban dynamics that have occurred following the implementation of the BRT in the city of Uberaba. More specifically, it analyzes the changes in commercial and real estate dynamics on Avenida Leopoldino de Oliveira. Qualitative and quantitative analysis, field research, and interviews with key stakeholders were used. The study reveals that the system adopted in the city was undersized and improved the quality of public transport in only a few respects. The avenue where the corridor was installed saw an increase in property vacancies and a reduction of approximately 30% in property values. Many businesses closed or moved away, and those that remained reported a reduction of approximately 30% in revenue. This research contributes to the discussion on public policies for sustainable mobility by raising questions about the adaptation of BRT systems to medium-sized cities.
Keywords: BRT; Urban mobility; Tertiary sector